Optimization of the geometry of double-chamber basin-type passive solar stills to maximize yield - Kelvin Mutevu Mwanzia; Stephen Ondimu; Patrick Ajwang (H2Open Journal, 2023)
Developing countries require simple low-technology methods to desalinate drinking water. Passive solar stills are an example of a simple low-technology innovation that can desalinate saline water for small populations. Compared to single-chamber solar stills, double-chamber solar stills have the potential of increasing the yield of solar stills due to an increased condensation surface area. An experiment was carried out to determine the optimal angle of double-chamber solar stills. The set-up comprised double-chamber solar stills with angles of 10°, 20°, 30° and 40°, with a control set-up of a 20° single-chamber solar still. The experiment was conducted in January 2022 at Juja in Kiambu County, Kenya. The double-chamber solar stills comprised an evaporation chamber and a condensation chamber. The dimensions of the chambers were 0.5 m × 0.5 m with a height of 0.25 m. The main assumptions were that there existed steady-state conditions and that the solar still was leakproof. The research found that the 40° double-chamber solar still had the highest yield of 3.756 l/m2/day and the 10° double-chamber solar still had the least yield of 1.644 l/m2/day. Comparing the 20° double-chamber still and the 20° single-chamber still (control), the double-chamber solar still had a higher external efficiency. HIGHLIGHTS The configuration of the double-slope single-chamber has not been experimented on before.; The geographical location is unique (Kenya (1°north of the equator)).;